A generalized bubbling/turbulent fluidized-bed reactor model - Thompson, Michael L.; Bi, Hsiaotao; Grace, John R. (Chemical engineering science, 1999)
A new reactor model is proposed as a means of representing fluidized-bed reactors which are subject to high enough gas velocities that they operate, or may operate, in the turbulent flow regime of fluidization. The model views the turbulent regime as filling the interval between fully two-phase behavior, represented by a generalized version of the two-phase bubbling bed model of Grace (1984), and a homogeneous (single-phase) structure, subject to axially dispersed plug flow. The two limiting models are merged into each other by allowing key parameters to vary continuously with the superficial velocity, U, using probabilistic averaging. The resulting model is shown to give good predictions in comparison with experimental data from the literature. In addition, it predicts a smooth transition from dense to dilute-phase fluidization, consistent with experimental trends.